2023
DOI: 10.3389/fcvm.2023.1080252
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations between dried fruit intake and cardiovascular disease: A Mendelian randomization study

Abstract: BackgroundPrevious studies have shown controversy about whether dried fruit intake is associated with cardiovascular disease. This study aimed to examine the potential causal effect of dried fruit intake on cardiovascular disease by conducting a two-sample Mendelian randomization study.MethodsWe used genome-wide association study (GWAS) summary statistics for MR analysis to explore the causal association of dried fruit intake with CVD. The inverse-variance weighted (IVW) method was used as the main analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…These components may have a significant effect on modulating CVD and diabetes risk ( 21 , 22 , 24 , 25 ). A recent MR study suggested that dried fruit intake reduces the risk of HF, total IS, and SVS, which further validates our findings ( 26 ).…”
Section: Discussionsupporting
confidence: 91%
“…These components may have a significant effect on modulating CVD and diabetes risk ( 21 , 22 , 24 , 25 ). A recent MR study suggested that dried fruit intake reduces the risk of HF, total IS, and SVS, which further validates our findings ( 26 ).…”
Section: Discussionsupporting
confidence: 91%
“…Dried fruits serve as nutrient-rich snacks, brimming with dietary ber, essential minerals, vitamins, and bioactive elements like avonoids and carotenoids. They offer notable health bene ts such as antioxidant, anti-in ammatory, anti-atherosclerotic, and anticancer properties [32][33][34][35]. These concentrated nutrients in dried fruits can play a signi cant role in combating oxidative stress and in ammation, two key factors in the development and exacerbation of various health conditions, including intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few studies have focused on the association between dried fruits and the risk of BE. Previous studies have suggested that dried fruit had a protective effect on various health-related outcomes such as cardiovascular disease and gastrointestinal disorders 42,43 . A previous MR study has also demonstrated that dried fruit reduced the risk of various cancers such as lung cancer and pancreatic cancer, suggesting a beneficial effect of dried fruit in disease prevention 44 .…”
Section: Discussionmentioning
confidence: 99%